The night swim - Goldin, Megan (St. Martin's Press, 2020)
"In The Night Swim, a new thriller from Megan Goldin, author of the "gripping and unforgettable" (Harlen Coben) The Escape Room, a true crime podcast host covering a controversial trial finds herself drawn deep into a small town's dark past and a brutal crime that took place there years before. After the first season of her true crime podcast became an overnight sensation and set an innocent man free, Rachel Krall is now a household name-and the last hope for thousands of people seeking justice. But she's used to being recognized for her voice, not her face. Which makes it all the more unsettling when she finds a note on her car windshield, addressed to her, begging for help. The small town of Neapolis is being torn apart by a devastating rape trial. The town's golden boy, a swimmer destined for Olympic greatness, has been accused of raping a high school student, the beloved granddaughter of the police chief. Under pressure to make Season Three a success, Rachel throws herself into interviewing and investigating-but the mysterious letters keep showing up in unexpected places. Someone is following her, and she won't stop until Rachel finds out what happened to her sister twenty-five years ago. Officially, Jenny Stills tragically drowned, but the letters insists she was murdered-and when Rachel starts asking questions, nobody seems to want to answer. The past and present start to collide as Rachel uncovers startling connections between the two cases that will change the course of the trial and the lives of everyone involved. Electrifying and propulsive, The Night Swim asks: What is the price of a reputation? Can a small town ever right the wrongs of its past? And what really happened to Jenny?"--